Community-Based Mangrove Ecotourism On Jeflio Island, Mayamuk District, Sorong District, Southwest Papua - Dwi Indah Widya Yanti; Ivonne M. Leiwakabessy (Universitas Muhammadiyah Sorong, 2023)
The aim of the study was to analyze the value of coastal local wisdom of the indigenous people of Jeflio Island for the development of mangrove ecotourism. In the research method used qualitative and quantitative approaches. Data analysis includes analysis of local wisdom values. Based on research, the Jeflio community has local wisdom in the form of calls for conservation known in the form of recommendations such as